Let's keep in-touch advocating for awareness and accepting of grief counseling as a means to great bereavement in Metro Manila - Tolosa, Timothy James S. (College of Fine Arts, University of the Philippines Diliman, 2018)
The social hierarchy of Filipinos and their stigma against mental health care and seeking out professional help inhibits Filipinos from seeking grief therapy, even when it becomes necessary for the griever. Instead, they would rather seek the insufficient advice and treatment from family and friends or decide not to seek help at all. This visual campaign aims to challenge those methods of thinking by illustrating situations where a griever requires the professional help despite the presence of their personal circles. Through this, its goal of raising the awareness and general acceptance of seeking professional help may be achieved. This campaign advertises in Touch Community Services in Makati City, one of the oldest and most well-staffed organizations based in Metro Manila since 1980. While they have services that can help a bereaved individual find counseling, their crisis hotline and professionals who specialize in treating various mental and interpersonal issues makes them one of the best institutions that foster mental health and emotional well-being.